(untitled) (Journal Of Educational and Psychological Researches, 2023)
The aim of this research is to find out the influence of Daniel’s model on the skills of the twenty-first century among the students of the scientific-fifth grade at the secondary and preparatory government morning schools for the academic year 2022- 2023. Two groups were chosen out of five groups for the fifth-scientific grade, one of which represents the experimental group that is taught by the Daniel model, and the other is the control group that is taught in the traditional method. The equivalence of the two research groups was verified with a set of variables. As for the research tool, a scale was developed by the researchers for the skills of the twenty-first century, in which they adopted the framework of the Partnership Organization for the Skills of the Twenty-first Century consisting of three main skills that include eleven sub-skills. The result revealed that there is a statistically significant difference at level (0.5) between the experimental and control groups in favor of the experimental group. In light of this result, a set of recommendations and conclusions were drawn up